Status of chloroquine and hydroxychloroquine in COVID-19 infection - Shahani, Savita Ramesh; Shahani, Lokesh R. (International Journal of Basic & Clinical Pharmacology, 2020)
COVID-19 causing virus is a single stranded RNA virus which has spread across the globe causing human respiratory tract infection. The novel virus which started from Wuhan was named as Wuhan coronavirus or 2019 novel corona virus (2019-nCov) by the Chinese researchers. The international committee on taxonomy of viruses named the virus as SARS-CoV-2 and the disease as COVID-19. There is preliminary in vitro evidence of the ability of CQ and HCQ to inhibit SARS-CoV-2 activity. Various small group clinical studies conducted in china indicated efficacy of chloroquine and hydroxychloroquine in Covid-19 cases but results were inconclusive. Based on these studies national agencies in various countries issued guidelines mentioning that chloroquine and Hydroxychloroquine are only to be used in clinical trials or emergency use programs. However, USFDA does not recommend use of both these drugs for treatment of COVID-19 cases. Chloroquine and hydroxychloroquine are known to produce dose dependent toxicity including fatal arrhythmias therefore its possible benefit has to be assessed against its risk. Large number of international and national studies are ongoing to assess exact status of chloroquine and hydroxychloroquine for treatment and prophylaxis of COVID-19 infection. Based on these results ICMR recommend to use hydroxychloroquine for prophylaxis of COVID-19 in India and hydroxychloroquine has been is included in schedule H1 hence they can be sold by pharmaceutical chemists only strictly with a valid prescription and require record to be maintained but chloroquine is still under schedule H which require to be sold with prescription.